Managerial Competency Analysis of Educators in Building Excellence Cadets - Musri Kona; Hadi Prayitno; Dhian Supardam; Nining Idyaningsih (International Journal of Science and Society, 2023)
Effective educational leadership provides the basis and places goals in an important position to change the norms in learning programs, increase productivity, and develop creative approaches to achieve maximum educational institution results and programs managerial competence possessed by aviation polytechnic educators in an effort to foster superior cadets. This research is qualitative with a case study design and uses three data collection methods, namely in-depth interviews, participant observation, and documentation studies. The research subjects were educators from the Medan Aviation Polytechnic who were selected using a purposive sampling technique. The following are the findings of this study: Managerial competence is seen in the planning, arrangement and coordination of cadet caregivers that can shape the development of academic, non-academic and disciplinary skills of cadets.